Acc El Analysis | Equations | Acceleration

Analytical Acceleration Analysis

Page 1 of 3

Dr. Keith Hekman

The vector loop equation for a fourbar linkage is ae jθ 2 + be jθ 3 − ce jθ 4 − de θ1 = 0 (1)

Assuming the initial vector loop equation has been solved using methods from chapter 4, we can take the derivative with respect to time to get & & & ae jθ 2 jθ 2 + be jθ 3 jθ 3 − ce jθ 4 jθ 4 = 0 Taking the derivative with respect to time to again results in & ae jθ 2 jθ 2

( )

( )

( )

(2)

( )
2

2

& & + ae jθ 2 jθ&2 + be jθ 3 jθ 3

( )

( )
2

2

& & + be jθ3 jθ&3 − ce jθ 4 jθ 4

( )

( )

2

& − ce jθ 4 jθ&4 = 0

( )

(3)

& & Setting ω = θ and α = θ& we have − ω 2 ae jθ 2 + jα 2 ae jθ 2 − ω 3 be jθ 3 + jα 3be jθ 3 + ω 4 ce jθ 4 − jα 4 ce jθ 4 = 0
2

(4)

This can be written as r r + a Att + a BAN + = −ω 2 ae j
2

r r − a BN − a Btt = 0 r a r a r a = jα 2 ae jθ 2 = jα 3 ae jθ 3 = jα 4 ae
jθ 4

( )

a a a

T

= −ω 3 ae j
2

T

6

= −ω 4 ae
2

j

T

ur goal is to find the unknown velocities based on the known parameters, i.e. to find α =

(a, b, , d , 2 , θ 3 ,θ , 2 , ω 3 , ω , 2 ) ω 4 = g ( , b, c, , θ , 3 ,θ 4 , ω , 3 , ω 4 , α )

(7

where the angular acceleration of the input link is given, and the position and velocity med. Arranging (4) so that the known values are on one side, and the unknowns are on the other and dividing by j, we have α 3be
θ

−α4

jθ 4

(

2

ae j 2 − α ae

θ

ω3

jθ 3

4

ce j

4

)

Z

(8

Taking the conjugate to get the second equation leads to α be − jθ 3
4

ce − j 4 =

9

[A] 
be j A= − θ 3 be Thus

  = [B ] α 4 
3

(

)

ce jθ 4  ce j 

B

Z  . Z 

11)

only the B matrix changes. The vector loop equation for a fourbar slider-crank linkage is ae jθ 2 − be jθ 3 − ce jθ 4 − de θ 1 = 0 Taking the derivative with respect to time. we have & ae jθ 2 ( jω 2 ) − be jθ 3 ( jω 3 ) − d = 0 Taking the derivative with respect to time again. we have & − ω 2 ae jθ 2 + jα 2 ae jθ 2 + ω 3 be jθ3 − jα 3be jθ 3 − d& = 0 2 2 (13) (14) (15) This also can be written as r r r r r a AN + a Att + a BAN + a BAtt − a B = 0 where r 2 a AN = −ω 2 ae jθ 2 r 2 a BAN = −ω 3 ae jθ 3 r & a B = d& r a AT = jα 2 ae jθ 2 r a BAT = jα 3 ae jθ 3 (16) (17) & The unknown variables in this equation are α3 and d& . &   1 Z   and B =   . we have 2 2 & jα 3be jθ 3 + d& = −ω 2 ae jθ 2 + jα 2 ae jθ 2 + ω 3 be jθ 3 = Z (18) Taking the conjugate to get the second equation leads to & be − jθ 3 (− jα 3 ) + d& = Z These two equations can be written in matrix form of (19) [A] &&3  = [B]   where  jbe jθ 3 A= − jθ 3 − jbe Thus α 3  −1  d&  = [ A] [B ] . Gathering the known values all on one side. Keith Hekman [ ]−1 [B] (12) Note that the A matrix is the same as in the velocity analysis.Analytical Acceleration Analysis Page 2 of 3 α3    4 Dr. 1 Z  α d  (20) (21) (22) .

Keith Hekman The vector loop equation for a fourbar inverted slider crank linkage is ae jθ 2 − be jθ 3 − ce jθ 4 − de θ 1 = 0 ( ) be jθ3 term. These two equations can be written in matrix form of  &&  α 3  ( ) (29) [A] b  = [B] where  e jθ 3 A =  − jθ 3 e Thus && b  −1   = [A] [B ] . Recall that the relationship between θ3 and θ4 remains fixed at 2 θ3 =θ4 +γ Taking the derivatives of this. so we need to group our equation accordingly. This leads to 2 2 2 && & b e jθ 3 + jα 3 be jθ3 + ce jθ 4 = −ω 2 ae jθ 2 + α 2 ae jθ 2 j − 2ωbe jθ 3 j + ω 3 be jθ 3 + ω 4 ce jθ 4 = Z . α 3  j be jθ 3 + ce jθ 4  Z  and B =   . both b and θ3 change so you have to differentiate by parts. (28) ( ) Taking the conjugate to get the second equation gives && b e − jθ 3 − jα 3 be − jθ3 + ce − jθ 4 = Z . − jθ 3 − jθ 4  − j be + ce Z   (30) ( ( ) ) (31) (32) .Page of 3 Dr. Thus the derivative is & ω 2 ae jθ 2 j − be jθ 3 − ω 3be jθ 3 j − ω 4 ce jθ 4 j = 0 . Again. taking the derivative results in 2 2 2 && & − ω 2 ae jθ 2 + α 2 ae jθ 2 j − b e jθ 3 − 2ωbe jθ3 j + ω 3 be jθ 3 − α 3be jθ 3 j + ω 4 ce jθ 4 − α 4 ce jθ 4 j = 0 (25) (24) & & One of the ωbe jθ 3 j terms comes from taking the derivative of be jθ3 and the other from ω 3 be jθ 3 . we have ω3 = ω 4 α3 = α 4 (26) (27) & Thus our unknown variables are α3=α4 and b& .

Sign up to vote on this title
UsefulNot useful